Synthetic pathways to water-soluble phthalocyanines and close analogs - Dumoulin, Fabienne; Durmuş, Mahmut; Ahsen, Vefa; Nyokong, Tebello (Elsevier Science Sa, 2010)
The different types of water-soluble phthalocyanines are presented and their synthesis is reviewed (C) 2010 Elsevier BV All rights reserved
Keywords: Phthalocyanine; Water soluble; Anionic; Cationic; Zwitterionic; Quaternization; Polyethylene glycol; Carbohydrate